STANDAR KOMPETENSI PENGELOLA KOPERASI SIMPAN PINJAM SYARIAH DI BMT TAQWA MUHAMMADIYAH PADANG - ERMAN ERMAN (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". This study discusses the topic of “Standar kompentensi pengelola koperasi simpan pinjam di BMT Taqwa Muhammadiyah Padang”. This study aims to determine the standard of competence that must be owned by management. The research used descriptive method with documentation approach. The results of the research are: 1) The manager must be able to make accurate planning for the progress of the business, 2) The manager must have a strategy in directing the members, 3) The manager must be able to build cooperation with other institutions, 4) The manager should be able to motivate the employees, 5) The manager must be able to supervise for operations.